PENGARUH STRUKTUR KEPEMILIKAN DAN DEWAN KOMISARIS TERHADAP TINGKAT PENGUNGKAPAN RISIKO PADA BANK SYARIAH - Ika Swasti Putri; Yuniatin TDKW (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
This research purpose to get empirical proof about the influences of profitability degree (ROA), public share ownership, commissioner with the Islamic economic background, and commissioner with background from Islamic banking supervisory institution to Risk Disclosure Index. This research is quantitative research and using secondary data form of an annual report on Islamic Banks in Indonesia for the period 2012-2018, with the samples used amounted to 11 Islamis Banks. This research uses purposive sampling to carry out sample selection. Statistic method that used for examining the hypothesis is multiple regression analysis. The result of this research showed that public share ownership and commissioner with the Islamic economic background are positive related significant with the level of risk disclosure. While the variables of profitability and commissioner with background from Islamic banking supervisory institution are not significant on the level of risk disclosure. Based on the research also found that the four variables simultaneously has influence to Risk Disclosure for 23,7%. Keywords: Risk Disclosure Index, profitability, public share ownership, commissioner.